Tradable SO-2-permits in the European Union: a practicable scheme for public utilities - Karl Ludwig Brockmann; Henrike Koschel; Tobias F. N. Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
In this paper, a practicable scheme of SO2-emission permits for European power producers is developed. Background is the second UN-ECE Sulphur Protocol from 1994 (Protocol of Oslo). After discussing some theoretical models of spatially differentiated permit schemes, evaluating the U.S. Acid Rain and RECLAIM Program, and considering the setting in the EU-15 countries, a scheme of locally undifferentiated emission permits is proposed which is distinguished by a high degree of both economic efficiency and market functioning. However, as our model simulations indicate, national deposition targets will be violated in all probability due to the scheme?s missing differentiation regarding the receptors. The risk of hot spots is addressed adequately by a differentiated bundle of countermeasures. The general economic impact of an EU-wide permit scheme is low, and, in terms of change in GDP, lower compared to a non-coordinated SO2 policy. The proposed mode of the initial permit allocation allows for early price signals and guarantees maximum static and dynamic efficiency. Balancing the interests of existing and new emitters, a long-term transition from the grandfathering to the free auction procedure is chosen.
Keywords: 330; Schwefeldioxid; Emissionsrechte; Elektrizitätswirtschaft; Wirtschaftspolitische Wirkungsanalyse; EU-Staaten